Business Marketing Management Strategy in the Modern Era Through 4P Marketing Strategies - Riza M. Yunus (Global Writing Academica Researching & Publishing, 2019)
In the modern era, the emergence of many new competitors in the business world causes businesses to need to make innovations in their marketing strategies. The marketing mix is one of the most effective strategies used in the modern era. This research will be carried out to analyze how to manage marketing strategies using the marketing mix. This research will be carried out using a qualitative approach. The data used in this research comes from various research results and previous studies relevant to the marketing mix. The results of this study found that there needs to be a change in marketing strategy due to the development of technology to continue attracting buyers. An understanding of the 4P strategy is essential for business people to maintain their existence among other competitors.